Knowledge Regarding Stoma Care among Nursing Students - Maharjan, Rozeena; Bhandari, Bhawana; Ojha, Anil Babu; Mugranti, Kopila; Jha, Jyanendra; Kafle, Uma; Dangol, Anamika; Mishra, Rupesh (Journal of Advanced Academic Research, 2023)
Background: Stoma and ostomy are Greek terms meaning mouth or opening done to treat several benign and malignant intestinal conditions, due to a change in bowel habits, anatomically modified by surgical creation of an opening in the abdominal wall involving parts of the gastrointestinal tract. Formation of colostomy is sometimes necessary and at other times mandatory. The colostomy patients wear a disposable pouch to collect the stool. A colostomy may be temporary or permanent, depending on the medical reason for the surgery. Objectives: To assess the knowledge of stoma care among PBN 3rd year student nurses and to identify the association of knowledge with the selected demographic variables. Methodology: A cross- sectional descriptive study was conducted among 39 student nurses of PBN 3rd year studying at the Hope International College with the objective to assess the knowledge regarding care of stoma among student nurses. Non-probability purposive sampling technique was used in this study and self-administered structured questionnaire was used in this study. The study was done in a private college of Lalitpur (Hope International College). Result: In this study 7.7% of the total student nurses had good knowledge, 89.7% student nurses had average knowledge and 2.6% student nurses had poor knowledge. Also found that there is no association between knowledge and other variables like age, experience, training, in-service education, care and interest as it showed no significance statistically. Conclusion: The study concluded that majority of student nurses had average knowledge regarding stoma care.